Treatment of chronic low back pain – new approaches on the horizon - Knezevic, Nebojsa Nick (J Pain Res, 2017)
Back pain is the second leading cause of disability among American adults and is currently treated either with conservative therapy or interventional pain procedures. However, the question that remains is whether we, as physicians, have adequate therapeutic options to offer to the patients who suffer from chronic low back pain but fail both conservative therapy and interventional pain procedures before they consider surgical options such as discectomy, disc arthroplasty, or spinal fusion. The purpose of this article is to review the potential novel therapies that are on the horizon for the treatment of chronic low back pain. We discuss medications that are currently in use through different phases of clinical trials (I–III) for the treatment of low back pain. In this review, we discuss revisiting the concept of chemonucleolysis using chymopapain, as the first drug in an intradiscal injection to reduce herniated disc size, and newer intradiscal therapies, including collagenase, chondroitinase, matrix metalloproteinases, and ethanol gel. We also review an intravenous glial cell-derived neurotrophic growth factor called artemin, which may repair sensory nerves compressed by herniated discs. Another new drug in development for low back pain without radiculopathy is a subcutaneous monoclonal antibody acting as nerve growth factor called tanezumab. Finally, we discuss how platelet-rich plasma and stem cells are being studied for the treatment of low back pain. We believe that with these new therapeutic options, we can bridge the current gap between conservative/interventional procedures and surgeries in patients with chronic back pain.